Peningkatan Motivasi Belajar melalui Program Pendampingan Pembelajaran Bagi Siswa Sanggar Belajar PPWNI Klang Malaysia - Subekti, Nur; Syah, Muhammad Fahmi Johan; Jariono, Gatot; Kartikasari, Evi Dwi; Pramudya, Redondo Sakti Adi; Bahri, Andi Syamsul; Kuswanty, Nur Helny (Universitas Muhammadiyah Surakarta, 2023)
Limited access to formal education coupled with the lack of teaching staff at the Sekolah Indonesia Kuala Lumpur (SIKL) study center has an impact on the decreased interest and motivation to study for children of migrant workers, especially those at the Pusat Pendidikan Warga Negara Indonesia (PPWNI) in the Klang region of Malaysia. This community service activity aims to help teachers at PPWNI Klang increase student learning motivation. Community service activities take the form of student learning assistance by involving Muhammadiyah Surakarta University students who take part in the Overseas KKN-Dik program. The learning methods applied during the learning assistance activities consist of 5 (five) stages, namely: (1) direct learning assistance to students on some subject matter which most students find difficult to understand, such as subjects: Mathematics, English, Science, and Physical Education; (2) discussion and question and answer; (3) Ice Breaking; (4) the method of giving interesting and fun quizzes to motivate student learning that is oriented towards the subject matter; and (5) giving rewards in the form of praise (oral) or gifts (goods). The results of this community service activity showed an increase in students' interest and motivation in learning, in addition to the observational data on 50 randomly selected students stated that learning assistance by involving students provided inspiration and students' interest in the world of education so that all students were interested in continuing their studies. higher education level. In addition, students increasingly understand the importance of education, especially in achieving future goals.